Soldering Characteristics And Thermomechanical Properties Of Pb-Free Solder Paste For Reflow Soldering - Ali Mokhtar, Mohd Najib; Mohammed Zulkifly, Abdullah; Saad, Abdullah Aziz; Che Ani, Fakhrozi; Samsudin, Zambri (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
A deep understanding in thermal characteristics of lead-free solder paste grades is one of the most crucial factors when dealing with reflow soldering process. These temperatures are critical parameters for proper settings of the real reflow process. This report is devoted to discussing the findings obtained during utilization of differential scanning calorimetry (DSC) and calculation using MATLAB to identify the latent heat, solidus and liquidus temperature, and surface tension applicable to numerically simulate the real process of reflow soldering. It can be stated that the equilibrium solidus and liquidus temperatures during solidification process are not a reversal of the melting process, with the solid phase equilibrium occurred at a lower temperature due to the difficulty of ß-Sn nucleation. Amount of heat energy released during solidification differs less than 10% for SAC405 and less than 1% for SAC105 with the latent heat of fusion during the melting process.